Cross-Continental Exploration: Comparative Analysis of Three Diverse Business Models - Rubini, Rizki Adriansyah; Hendrayati, Hendrayati; Rahman, Fahrul Fauzi; Sultan, Mokh Adib; Surachman, Eka (Jurnal Ilmu Manajemen dan Bisnis, 2024)
This article analyzes the application of the Business Model Canvas (BMC) in three companies from Indonesia, Romania, and Brazil operating in the food and agriculture sectors. The study uses a descriptive-analytical approach to understand how these companies adjust their strategies to local and global market contexts. Findings indicate that effective customer segmentation, diverse distribution channels, and strategic partnerships are crucial for their success. Additionally, innovation and digital transformation significantly contribute to the resilience and sustainability of these companies. The results provide practical insights for entrepreneurs and policymakers in designing more adaptive and sustainable strategies in dynamic markets.